Current insights into anti-HIV drug discovery and development: a review of recent patent literature (2014–2017). (3rd April 2018) - Zuo, Xiaofang; Huo, Zhipeng; Kang, Dongwei; Wu, Gaochan; Zhou, Zhongxia; Liu, Xinyong; Zhan, Peng
ABSTRACT: Introduction : To deal with the rapid emergence of drug resistance challenges, together with the difficulty to eradicate the virus, off-target effects and significant cumulative drug toxicities, it is still imperative to develop next-generation anti-HIV agents with novel chemical classes or new mechanisms of action. Areas covered : We primarily focused on current strategies to discover novel anti-HIV agents. Moreover, examples of anti-HIV lead compounds were mainly selected from recently patented publications (reported between 2014 and 2017). In particular, 'privileged structure'-focused substituents decorating approach, scaffold hopping, natural-product diversification and prodrug are focused on. Furthermore, exploitation of new compounds with unexplored mechanisms of action and medicinal chemistry strategies to deplete the HIV reservoir were also described. Perspectives that could inspire future anti-HIV drug discovery are delineated. Expert opinion : Even if a large number of patents have been disclosed recently, additional HIV inhibitors are still required, especially novel chemical skeletons displaying a unexploited mechanism of action. Current medicinal chemistry strategies are inadequate, and appropriate and new methodologies and technologies should be exploited to identify novel anti-HIV drug candidates in a time- and cost- effective manner.